Behaviour of concrete by using artificial aggregates a review - Manju, K; Dhanush Kumar, B; Suresh Kumar, S; Nirmal Kumar, S (International Journal of Engineering and Technology, 2018)
Natural aggregate is not an environmental friendly material due to its destructive resource consuming nature. GGBS is a byproduct of steel industries, whereas GGBFS mixed with cement of 1:2 ratio making an artificial aggregate, whereas hardening powder used to spray made upon artificial aggregate to develop the strength of concrete. The basic properties of natural and artificial aggregates were determined. The mix design to be determined obtained for conventional concrete of control mix of grade M 25. The different mix proportions were prepared by replacement of 20, 40, 60, 80, 100 of natural aggregate instead of artificial aggregate. To check the compressive strength, split tensile strength determine. Based on the result we choose optimum percentage of aggregate and make it and concrete to determine the durability properties of concrete compared with natural aggregate.Â Â